Association of Genetic Variants in IGF2-Related Genes With Risk of Metabolic Syndrome in the Chinese Han Population - Gui, Weiwei; Liang, Julong; Lin, Xihua; Shi, Nanjing; Zhu, Yiyi; Tan, Bowen; Li, Hong (Frontiers in Endocrinology, 2021)
Aims To explore associations between polymorphisms of IGF2-related genes including H19, IGF2, IGF2BP2 and IGF2R and Metabolic syndrome (MetS) susceptibility in the Chinese Han population. Methods 66 subjects with MetS and 257 control subjects were collected for inclusion in a case-control study. PCR-RFLP was used to investigate polymorphisms in the H19, IGF2, IGF2BP2 and IGF2R genes. Elisa was used to detect the serum IGF2 concentrations. Results Females carrying the GG and AG genotypes of rs680 (IGF2) exhibited a lower risk of MetS, compared with those harboring AA (adjusted OR = 0.388, p = 0.027), while GG and AG genotypes were associated with lower fasting glucose and HbA1c. In males, the Waist-to-Hip Ratio (WHR) and the level of TG were significantly higher in GG and AG genotypes than in the AA genotype of rs680 in IGF2. Levels of HDL-c were lower in men with GG and AG genotypes compared with those carrying the AA genotype. Serum IGF2 concentrations did not change among different genotypes. Finally, multifactor dimensionality reduction (MDR) analysis identified interactions between four polymorphisms: rs3741279 (H19), rs680 (IGF2), rs1470579 (IGF2BP2) and rs629849 (IGF2R). Conclusions Our study suggests that IGF2-related genes including H19, IGF2, IGF2BP2 and IGF2R genes may play pivotal roles in the development of MetS.